Infant health: a community-based assessment and educational intervention in two rural communities in the Eastern Cape. - Kuzeeko, Faith (Rhodes University, Faculty of Pharmacy, Pharmacy, 2021)
South Africa is on track to attaining the 2030 Agenda on reducing under-five deaths to 25 deaths per 1000 live births at its current momentum, however an unacceptable amount of infants are still at risk from preventable illnesses. Malnutrition is the major underlined cause of infant mortality rates in South Africa. Exclusive breastfeeding rates are low nationwide due to low exposure to breastfeeding information, some mothers having other commitments and others having breastfeeding difficulties. Implementation and expansion of simple, cost-effective interventions, such as exclusive breastfeeding for six months to reduce and/or prevent infant mortality rates, remains low in South Africa. The aim of the study was to determine one infant health issue of major concern to participants in two rural villages in the Eastern Cape, namely Glenmore and Ndwayana. The identified infant health issue was used to design an educational intervention in the villages. This was the second phase of this study. A community-based participatory approach was utilized in which the Angus Gillis Foundation, a non-profit organization that works in these communities, was one of the stakeholders. Stock status of WHO priority medicines for infants, semi-structured interviews and focus group discussions were carried out during the baseline study. The intervention phase contained pre-2 intervention semi-structured interviews with ten pregnant women followed by an educational intervention with nine out of the ten; and finally, a post-intervention with seven out of the ten women. A questionnaire was completed by members of the Angus Gillis Foundation to provide feedback on the sustainability of the intervention. Semi-structured interviews revealed that medicines stocked at the clinic parallel those indicated in the WHO priority medicines list for infants. The results from the focus group discussions indicated that mothers do not exclusively breastfeed their infants during the first six months. Pre- and post-intervention results on exclusive breastfeeding illustrated a positive change in participants' knowledge and intent to breastfeed exclusively for six months. They showed a better understanding of the importance of exclusive breastfeeding and indicated a more focussed intention and confidence to carry out optimal breastfeeding practices. In the questionnaire the members of the Angus Gillis Foundation stated that the intervention is sustainable as it was linked with the existing networks. These include educational programs carried out in the villages by the foundation together with positive health champions, community health workers and women self-help groups; which will be able to build on the present knowledge base. Finally, the study also included the design of a booklet on the identified infant health issue. In conclusion, participants highlighted lack of understanding regarding breastfeeding as an issue of concern during the baseline phase of the study. This community-based educational intervention improved the understanding of breastfeeding among the participants, resulting in a positive change in perception with regards to exclusive breastfeeding practices.
Keywords: Angus Gillis Foundation (South Africa); Infants -- Mortality -- South Africa; Infants -- Health and hygiene -- South Africa; Breastfeeding -- South Africa -- Eastern Cape; Infants -- Care -- Equipment and supplies; Infants -- Care -- South Africa -- Eastern Cape -- Case studies; Children -- Mortality -- South Africa; High throughput screening (Drug development)